2015
DOI: 10.1021/jacs.5b03945
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Electrostatic Interactions Drive Functional Evolution in the Alkaline Phosphatase Superfamily

Abstract: It is becoming widely accepted that catalytic promiscuity, i.e., the ability of a single enzyme to catalyze the turnover of multiple, chemically distinct substrates, plays a key role in the evolution of new enzyme functions. In this context, the members of the alkaline phosphatase superfamily have been extensively studied as model systems in order to understand the phenomenon of enzyme multifunctionality. In the present work, we model the selectivity of two multiply promiscuous members of this superfamily, nam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
99
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(107 citation statements)
references
References 84 publications
6
99
1
Order By: Relevance
“…4,5 We have observed that rather modest changes in the reactivity of a substrate can have significant, conspicuously observable effects on the nature of a TS without changing the chemical mechanism or rate-determining step. The fact that AP catalyzes the hydrolysis of the whole range of LGs largely bolsters previous notions about catalytic promiscuity in AP 9,28,58,59 and similar systems, 60,61 namely that the enzyme is capable of stabilizing TSs with a variety of structures and that it does so by different means. Nonetheless, our results indicate significant departures from the previously proposed reaction pathways taken by AP’s phosphate ester substrates.…”
Section: Discussionmentioning
confidence: 55%
“…4,5 We have observed that rather modest changes in the reactivity of a substrate can have significant, conspicuously observable effects on the nature of a TS without changing the chemical mechanism or rate-determining step. The fact that AP catalyzes the hydrolysis of the whole range of LGs largely bolsters previous notions about catalytic promiscuity in AP 9,28,58,59 and similar systems, 60,61 namely that the enzyme is capable of stabilizing TSs with a variety of structures and that it does so by different means. Nonetheless, our results indicate significant departures from the previously proposed reaction pathways taken by AP’s phosphate ester substrates.…”
Section: Discussionmentioning
confidence: 55%
“…Thus, it was not until the 1976 work of Warshel and Levitt 51 that the major role of electrostatic effects in catalysis was clearly demonstrated. However, since 1976, it has become quite clear that electrostatic effects are central to catalysis 1 (and more recently also to enzyme functional evolution 157 ). The nature of the electrostatic stabilization has been recognized first in Ref.…”
Section: Preorganization Is the Key Factor In Enzyme Catalysismentioning
confidence: 99%
“…For example, enzymes catalyzing phosphoryl transfer reactions are known to have backup active site residues for the catalysis of promiscuous reactions [29,30]. For example, enzymes catalyzing phosphoryl transfer reactions are known to have backup active site residues for the catalysis of promiscuous reactions [29,30].…”
Section: Rab5a Might Also Employ Two Different Hydrolysis Mechanismsmentioning
confidence: 99%
“…Structural plasticity is a general concept governing the function of many proteins. For example, enzymes catalyzing phosphoryl transfer reactions are known to have backup active site residues for the catalysis of promiscuous reactions [29,30]. In case of GTPases, structural plasticity is even more critical to ensure versatility in effector binding and consequently the effective activation/inactivation of GTPases.…”
Section: Rab5a Might Also Employ Two Different Hydrolysis Mechanismsmentioning
confidence: 99%